Echoes of the past: St Dunstan and the heavenly choirs of St Augustine's Abbey, Canterbury, in Goscelin's Historia translationis S. Augustini. (December 2019) - Sawicka-Sykes, Sophie
Abstract: The Historia translationis S. Augustini (1098 × 1100), composed by Goscelin of Saint-Bertin as part of a hagiographical cycle for St Augustine's Abbey, contains several previously overlooked allusions to St Dunstan's vision of heavenly virgins. I argue that Goscelin drew upon the Dunstan legend to justify Abbot Scotland's renovation work on St Augustine's between 1072 and 1087. The article first of all considers how the oratory of the Anglo-Saxon abbey was presented as a locus of divine praise in the first known hagiography of Dunstan. I then show how Dunstan's eleventh-century hagiographers at Christ Church cathedral responded to the original vision by crafting competing narratives of heavenly choirs. Finally, an analysis of the Historia translationis reveals how Goscelin reappropriated the legend, depicting the oratory, and the crypt that came to replace it, as the abode of celestial spirits whose praise echoed the community's liturgical devotions.